1999
DOI: 10.2307/2667032
|View full text |Cite
|
Sign up to set email alerts
|

The Search-Transfer Problem: The Role of Weak Ties in Sharing Knowledge across Organization Subunits

Abstract: and three anonymous reviewers for ASQ. I thank Linda Johanson for editorial guidance. Research support from the Norwegian Research Council is gratefully acknowledged.This paper combines the concept of weak ties from social network research and the notion of complex knowledge to explain the role of weak ties in sharing knowledge across organization subunits in a multiunit organization. I use a network study of 120 new-product development projects undertaken by 41 divisions in a large electronics company to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

125
3,954
12
157

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 4,664 publications
(4,248 citation statements)
references
References 29 publications
125
3,954
12
157
Order By: Relevance
“…Second, the curvilinear relationship that we find adds to the discussion on the strength of weak vs. strong ties and the notion of over-embeddedness (Uzzi, 1997;Hansen, 1999;Granovetter, 1973). The finding contrasts with previous research reporting a positive linear relationship between environmental threats and relational strength (Gulati, 1995;Beckman et al, 2004;Blankenburg Holm et al, 1999).…”
Section: Introductioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Second, the curvilinear relationship that we find adds to the discussion on the strength of weak vs. strong ties and the notion of over-embeddedness (Uzzi, 1997;Hansen, 1999;Granovetter, 1973). The finding contrasts with previous research reporting a positive linear relationship between environmental threats and relational strength (Gulati, 1995;Beckman et al, 2004;Blankenburg Holm et al, 1999).…”
Section: Introductioncontrasting
confidence: 93%
“…This gap refers also to a certain neglect of the costs of forming and maintaining strong ties (e.g. Hansen, 1999) in the literature on MNC subsidiaries.…”
Section: Antecedents Of Subsidiary Relational Embeddednessmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of a focal point (orchestrator), value must be created and extracted from the network [Kogut, 2000]; effective creation and extraction of value hinge on certain deliberate, purposeful actions. Several authors such as [Doz, 1996, Gulati and Gargiulo, 1999, Hansen, 1999 previously observed that an orchestrator can assess the value of the relevant knowledge and capabilities residing at different points in the network and can arrange their transfer to other networks where required. From a technological perspective, web service orchestration coordinates the time-dependent sequence of web services by using a process flow.…”
Section: Characteristic Descriptionmentioning
confidence: 99%